Improvement of Duncan-Chang Constitutive Model of Argillaceous Siltstone Soil-Rock Mixture - ZHANG Han; YI Chenglong; LIU Zhongfan; CHEN Kangpei; CHEN Yanjiang (Renmin Zhujiang)
Different from the stiff soil-rock mixture (S-RM), the soft blocks will break during the shear failure of the soft S-RM, so the shear mechanical properties of soft S-RM are affected by the block breakage properties. In order to accurately predict the deformation of soft S-RM slope and evaluate the engineering stability, it is urgent to study the shear mechanical properties and constitutive models of S-RM. The shear mechanical properties and the block breakage properties of S-RM were analyzed by the large-scale triaxial test. Based on the relationship between breakage ratio Br and damage ratio Rf, the Duncan-Zhang constitutive model suitable for S-RM was improved. The results show that after the shear failure of soft S-RM, the content of the block size group (5–60 mm) decreases, while that of the fine soil size group (<2 mm) increases. The block breakage ratio reaches 20% under high confining stress. With the increase in confining stress, the breakage ratio and shear strength of S-RM increase. With the increase in the breakage ratio Br, the damage ratio Rf decreases linearly. Compared with the experimental data, the improved Duncan-Chang constitutive model can more reasonably characterize the stress-strain characteristics of S-RM.